ROLE OF PUBLIC LIBRARIES IN ENHANCING INFORMATION ACCESS THROUGH REFERENCE SERVICES: EVIDENCE FROM GOA - Verenkar, Deepika Gokuldas Shet; Bhakt, Vaishali Umakant (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
Public libraries play a vital role in providing equitable access to information through traditional and digital reference services. This study examines the role of public libraries in Goa in enhancing information access through reference services. The objectives include identifying available reference services, evaluating their effectiveness, assessing user satisfaction, and suggesting improvements. The study adopts a survey methodology using questionnaires administered to library users and librarians. Data are analysed using descriptive statistics and percentage analysis. Findings indicate that reference services significantly improve information access, while digital services such as Web OPAC, e-resources, and online communication enhance user convenience. Challenges include limited ICT infrastructure, staffing, and user awareness. The study concludes that strengthening digital reference services and continuous staff training can improve public library services in Goa.